The Role of Radiotherapy in Soft Tissue Sarcoma on Extremities With Lymph Nodes Metastasis: An IPTW Propensity Score Analysis of the SEER Database - Qiu, Xinzhu; He, Hongbo; Zeng, Hao; Tong, Xiaopeng; Liu, Qing (Frontiers in Oncology, 2021)
Background: Soft tissue sarcomas on extremities with regional lymph nodes metastasis (STSE-RLNM) is a devastating situation. Optimizing therapeutic approaches is vital but hampered by a shortage of randomized trials. We used a population-level database to evaluate radiotherapy's impact on sarcoma-specific survival (SSS) and overall survival (OS) for surgery for STSE-RLNM. Methods: We retrospectively screened data from the SEER database (2004-2015), and 265 patients with STSE-RLNM who received surgery, with (134) or without (131) radiotherapy, were enrolled in this study. A propensity score-matched analysis with the IPTW Kaplan-Meier curve was created. The log-rank test and Cox regression analysis were performed to compare SSS and OS in patients with and without radiotherapy. Further analysis of radiotherapy time was conducted, and the Kaplan-Meier curve and the log-rank test were done. Landmark analysis was introduced to attenuate the immortal bias. Results: In the original unadjusted cohort the radiotherapy + surgery group is associated with improved SSS (HR, 0.66; 95% CI, 0.47-0.91; p=0.011) and OS (HR, 0.64; 95% CI, 0.47-0.88; p=0.006). And this significant treatment effect was also noted in IPTW-adjusted Cox regression either on SSS (HR, 0.65; 95% CI, 0.45-0.93; p=0.020) or on OS (HR, 0.64; 95% CI, 0.46-0.91; p=0.013). The Kaplan-Meier curve and log-rank test showed that Pre- and postoperative radiotherapy was not related to SSS (p=0.980 or OS (p=0.890). Conclusion: Radiotherapy and surgery has a significant benefit on the prognosis of patients with STSE-RLNM compared to surgery alone. These findings should be considered when making treatment decisions for them.